Chromosomal polymorphism in forpus xanthopterygius (Psittaciformes: Aves) - de Lucca, Edmundo José [UNESP]; de Marco, Dagmar Aparecida [UNESP] (Firenze University Press, 1983)
Karyotypic analyses of 41 specimens of Forpus xanthopterygius (Psit-taciformes: Aves) reveal a diploid number of 86 and three different karyotypes were observed. A chromosomal polymorphism is present which involves two pairs of chromosomes. It is suggested that the observed polymorphism resulted from a translocation involving pairs 1 and 5. The significance of this intrapopulation variation is discussed. © 1983 Taylor & Francis Group, LLC.